A Book Review of Bill Bryson’s a Walk in the Woods - Aulia, Asri Novia (LANTERN (Journal on English Language, Culture and Literature), 2016)
A Walk in the Woods is a true story about the author’s experience crossed the Appalachian Trail. Bill Bryson’s book consists of twenty one chapters that mostly talk about his experience, history and information about Appalachian Trail. In his novel he starts to collect the information about Appalachian Trail from the book and from experts, buy things for hiking and invite hiking companions. Stephen Katz accepted Bryson’s invitation to cross the Appalachian Trail. However, the interesting fact is neither Katz nor Bryson has experience of hiking. Their journey will be their first experience of hiking and they choose the hardest one.